MENGURANGI KEKERASAN TERHADAP ANAK BERBASIS PENDEKATAN PENDIDIKAN MULTIKULTURAL - Nur Kholis (IAIN Ponorogo, 2014)
Abstract: Humans have their own potential as an instrument to perfect their existence. In the process of perfecting, they always do some processes as well as social interactions to optimize any potential they had by synchronizing internal and external poten-tials of their social environment. A phenomenon shows that there are two possibilities resulted by the process: harmony or clash. The process of harmony is indicated by accomplishment of any objectives or needs of each individual that does the social interaction. On the contrary, the clash process will happen if the interactions turn to violence on weak/poor individual or group, either structurally or culturally, socially, and economically. One of causes of the clash resulting violence is the absence of social control, imbalance of hierarchical interaction, social imbalance and poor economy. Multicultural education can be set as an approach in learning/education in Indonesia by firstly examining its philosophical background and educational theory which, then, leads to the method(s) and technique(s) of learning/education to shape generation that have the following characteristics: tolerated, social-characterized, and aware to certainty of diversity as sunatullah that hopefully results in decreasing clash phenomena which lead to any violence or conflict.